Who Feels Disadvantaged? Reporting Discrimination in Surveys - Daniel Auer; Didier Ruedin (Migrants and Expats: The Swiss Migration and Mobility Nexus, 2019)
In this chapter, we seek to shed light on the mechanisms of perceived discrimination: Who, among recent immigrants, is more likely to feel discriminated against and report it when asked in a survey? Social scientists typically define discrimination as an observable and unjust difference in the treatment of distinct groups. To personally feel discriminated against, people must be aware of the differential treatment and perceive it as unjust. We show that reporting discrimination when asked in a survey depends substantially upon individual traits, including aspects that shape whether discrimination is accepted and whether immigrants feel attached to the host society. Although respondents report less discrimination if their job situation has improved after migration, people more likely report discrimination when they originate from countries in which the national legislature represents ethnic minority groups relatively well. Earlier difficulties related to the migration process and the lack of supporting networks continue to affect the perception of unfair treatment. Moreover, we show that individuals distinguish to a surprising degree between discrimination in and outside the work environment. For instance, when they are proficient in the local language, respondents often report discrimination in the workplace but not in a public environment. This distinction between discrimination in the workplace and discrimination in public also depends strongly upon the immigrant's origin. We conclude that contemporary individual-level measures and policy recommendations merely approximate discriminatory patterns; we urge future research to consider factors that affect individual perception of discrimination.
Keywords: 330; perceived discrimination; immigration; workplace; public sphere; ethnic minority; Switzerland